EVALUASI STABILITAS MERCU BENDUNG SITAKKURAK DI BARUS KABUPATEN TAPANULI TENGAH - Nelson Hutahayan; Ronaldo M.P. Lumbantoruan (Prodi Teknik Sipil Fakultas Teknik Universitas Darma Agung, 2020)
The river is very important for human life, one of which is as a source of water that can be used to meet the needs of irrigation, drinking water supply, household industry water needs and others. Aek Sirahar River is very potential for agricultural land that has been carried out since Dutch times. Sitakkurak weir with an area of ​​± 2200 ha of paddy fields in Central Tapanuli Regency, this weir will irrigate paddy fields for 3 (three) districts of Central Tapanuli Regency namely Barus, North Barus, Adam Dewi Districts. The effective width of the Sitakkurak weir is 62.56 m with a height of 2 m lighthouse. The Sitakkura dam uses a round type with an olak pool like a sinking type. In searching for the Sitakkurak Dam Flood Discharge, there are three methods used, namely Hasper, Rational and Mononobe methods. From the results of the hydrological analysis calculation, it is obtained a Q100 year plan = 1034.76 m3 / sec, with one radius, and the type of sink sink. In calculating the stability of the weir under normal water level conditions the elevation of the water level = + 11.50 m, and the height of the water level at the time of the Flood = + 15.04. Dam stability control is by earthquake to the bolt sfguling = 1,584> 1.30; without earthquake: on rolling Sfguling = 2.80> 1.50; against sliding Sfgeser = 2.109> 1.30; without earthquake to slip Sfgelincir = 2,929> 1.50. From the control calculation it can be concluded that the Sitakkurak Dam is safe from shear, rolling and uplift forces, and it can be concluded that the soil where the weir is built can support the structure of the weir.